2018
DOI: 10.1525/abt.2018.80.8.578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Online, Inquiry- & Mentor-Based Laboratory on Science Attitudes of Students in a Concurrent Enrollment Biology Course: The PlantingScience Experience

Abstract: The goal of this project was to determine the impact of supplementing a concurrent enrollment (CE; also called dual enrollment) nonmajors biology course with online mentoring from professional scientists via the PlantingScience (PS) program (http://plantingscience.org). Student attitudes and motivation toward science were measured using the Test of Science-Related Attitudes (TOSRA) questionnaire as well as open-ended questions. Students in both the experimental group (CE biology course supplemented with PS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Liaisons also learned strategies for providing high-quality feedback to students and mentors. Involving PlantingScience liaisons is a practical approach to address the quality, consistency, and frequency of scientist–student interactions (Desy et al, 2018; Scogin & Stuessy, 2015; Peterson, 2012). Previous studies found that the different environments and cultures in which teachers and scientists usually work can create challenges within STSPs (Carr, 2002; Houseal et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Liaisons also learned strategies for providing high-quality feedback to students and mentors. Involving PlantingScience liaisons is a practical approach to address the quality, consistency, and frequency of scientist–student interactions (Desy et al, 2018; Scogin & Stuessy, 2015; Peterson, 2012). Previous studies found that the different environments and cultures in which teachers and scientists usually work can create challenges within STSPs (Carr, 2002; Houseal et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the specific content delivery styles, this could result in potential differences in student engagement compared to other universities that deliver learning resources via distance/online mode. As highlighted by many researchers, there is considerable opportunity to use online delivery modes to provide highly engaging material that extends student learning (Baxley, 2018;Desy et al, 2018;Johnson et al, 2021;Sharma et al, 2020). The scope of this study was somewhat limited, as we only considered approximately 300 students from one year.…”
Section: Limitationsmentioning
confidence: 99%
“…Preparing mentor liaisons to work collaboratively with teachers helps provide higher quality feedback to students and mentors. Involving mentor liaisons is a practical approach to address the quality, consistency, and frequency of scientist-student interactions (Desy et al, 2018;Peterson, 2012;Scogin & Stuessy, 2015). Previous studies identified challenges of having teachers and scientists work together due to the differences between the environments and cultures in which each group normally works (Carr, 2002;Houseal et al, 2014).…”
Section: Collaborative Teacher/mentor Liaison Professional Developmentmentioning
confidence: 99%
“…Skillfully orchestrating such student experiences requires practice and support. In addition, the difference in the amount, content, and timing of mentoring is associated with differences in the student experience in PlantingScience (Adams & Hemingway, 2014;Desy et al, 2018;Peterson, 2012;Scogin, 2014;Scogin, 2016;Scogin & Stuessy, 2015). Trained mentor liaisons can help to reduce these inconsistencies.…”
Section: Prior Research On Plantingsciencementioning
confidence: 99%